2021
DOI: 10.3390/ijms221910304
|View full text |Cite
|
Sign up to set email alerts
|

PIF4 and PIF4-Interacting Proteins: At the Nexus of Plant Light, Temperature and Hormone Signal Integrations

Abstract: Basic helix-loop-helix (bHLH) family transcription factor PHYTOCHROME INTERACTING FACTOR 4 (PIF4) is necessary for plant adaption to light or high ambient temperature. PIF4 directly associates with plenty of its target genes and modulates the global transcriptome to induce or reduce gene expression levels. However, PIF4 activity is tightly controlled by its interacting proteins. Until now, twenty-five individual proteins have been reported to physically interact with PIF4. These PIF4-interacting proteins act t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 140 publications
0
15
0
Order By: Relevance
“…The TF WRKY34 interacts with the VQ20 protein to regulate pollen development and function 39 . The bHLH family TF PIF4 is necessary for plants to adapt to light and high ambient temperature, and interaction between PIF4 and PIF4 interacting proteins establishes a strong network for plants to respond to changes in the environment 40 . In addition, phytochrome interaction factors PIF4 and PIF5 negatively regulate anthocyanin synthesis in Arabidopsis seedlings under red light 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The TF WRKY34 interacts with the VQ20 protein to regulate pollen development and function 39 . The bHLH family TF PIF4 is necessary for plants to adapt to light and high ambient temperature, and interaction between PIF4 and PIF4 interacting proteins establishes a strong network for plants to respond to changes in the environment 40 . In addition, phytochrome interaction factors PIF4 and PIF5 negatively regulate anthocyanin synthesis in Arabidopsis seedlings under red light 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there has been little information on PIFs in crops. In our study, we found that the sequence of PIF4 protein was distinct from other PIFs homologs in rice, and it shows decreased gene expression followed by HL exposure from dark (Figure 3B-C), suggesting like PIF1, activated phyB interacts with PIF4 and induces its phosphorylation and degradation under light irradiation (Xu & Zhu, 2021).…”
Section: Discussionmentioning
confidence: 75%
“…The transcription of PIF4 is induced by high ambient temperatures [ 40 ], thereby enhancing the accumulation of PIF4 protein. The increased PIF4 protein induces hypocotyl growth by activating the expression of auxin biosynthetic genes such as YUCCA8 (YUC8) , CYP79B2, and TAA1 ; auxin signaling genes such as IAA19 and IAA29 ; growth-promoting genes such as ATHB2 and LNGs ; and brassinosteroid biosynthetic genes such as BES1 and BZR1 [ 41 ]. The evening complex (EC), which consists of ELF3 , ELF4 , and LUX , mediates the warm-temperature activation of PIF4 mRNA expression [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous studies have established that PIF4 is a core hub of thermomorphogenesis when plants are exposed to high ambient temperatures [ 40 , 41 , 46 , 47 , 48 , 49 , 50 ]. However, whether PIF4 also regulates HSR when plants are subjected to severe HS and the mechanistic details underlying this proceeding remains unclear.…”
Section: Introductionmentioning
confidence: 99%